Young adults' stigmatizing perceptions about individuals with skin cancer: the influence of potential cancer cause, cancer metaphors, and gender. Issue 5 (4th May 2022) - Bowers, Jennifer M.; Nosek, Sarah; Moyer, Anne
Abstract: Objective: This study examined the influence of three potential predictors of stigmatising cancer perceptions: the controllability of the cancer cause, metaphors used to describe the cancer experience, and the target's gender. Method: 306 undergraduates ( M age = 20) were recruited via subject pool, balancing males and females. Participants read a fictitious post by a patient/blogger with skin cancer that described different potential causes for their cancer varying with respect to its controllability, used varying types of commonly invoked cancer metaphors, and indicated their gender with names. Main outcome measures: Potential stigmatisation of the blogger in the form of negative affective responses, perceptions of flawed character, desired social distance and expectations for post-traumatic growth were assessed using mixed methods. The perceived age of the blogger and expectations for their survival were also explored. Results: More blame, less sympathy, and less favourable perceptions of character were ascribed to the hypothetical blogger when their cancer was described as due to their lifestyle rather than genetics and thus potentially construed as more controllable. Females using a war metaphor resulted in more positive responses compared to a female using no metaphorical language. Conclusion: Stigmatisation of individuals with skin cancer may depend on the potential cause of cancer, and to some extent, metaphors and gender.